2019
DOI: 10.1002/rob.21890
|View full text |Cite
|
Sign up to set email alerts
|

Improvements to and large‐scale evaluation of a robotic kiwifruit harvester

Abstract: The growing popularity of kiwifruit orchards in New Zealand is increasing the already high demand for seasonal labourers. A novel robotic kiwifruit harvester has been designed and built to help meet this demand [H. A. Williams et al. Biosystems Eng. 181 (2019), pp. 140–156]. Early evaluations of the platform have shown good results with the system capable of harvesting 51.0% of 1,456 kiwifruit in four bays with an average cycle‐time of 5.5 s/fruit. However, the harvester's high cycle‐time, and high fruit loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…A later improved robot [55] can detect 90% of the kiwi in the orchard, using Faster-Regions with Convolutional Neural Networks (RCCN). Specifically, 86.0% of kiwis can be picked by the improved device (55.8% of all kiwis).…”
Section: A Picking Robot With a Route Navigationmentioning
confidence: 99%
“…A later improved robot [55] can detect 90% of the kiwi in the orchard, using Faster-Regions with Convolutional Neural Networks (RCCN). Specifically, 86.0% of kiwis can be picked by the improved device (55.8% of all kiwis).…”
Section: A Picking Robot With a Route Navigationmentioning
confidence: 99%
“…Reducing the cycle time for harvesting represents a vital role for the robot industry. The review showed a kiwi harvester could achieved the shortest cycle time of 1 s due to a low-cost and effective manipulator [52,53]. The damage caused during the grasping of the fruit is one of the main concerns in dealing with manipulators [54].…”
Section: Unmanned Ground Vehicles (Ugvs)mentioning
confidence: 99%
“…Williams, Zhang, SEPÚLVEDA, Mu, Chen, Li, and Liu et al [64][65][66][67][68][69][70][71][72][73][74][75][76] , have developed multi-arm robots for kiwifruit, tomato and grape harvesting and other high-density fruit respectively. Facing the new demand of the new urban production-leisure integrated industry, different humanoid dual-arm harvesting robots have been developed by Peng, and Chen et al [69,70] , which adopt parallel operation mode with the help of on-head RGB-D cameras and in-hand RGB-D cameras.…”
Section: Commercial Non-selective Agricultural Working Robotsmentioning
confidence: 99%